Barriers and Drivers of Planning for Climate Change Adaptation across Three Levels of Government in Canada. (27th May 2018) - Oulahen, Greg; Klein, Yaheli; Mortsch, Linda; O'Connell, Erin; Harford, Deborah
ABSTRACT: This study investigates the factors that constrain and enable adaptation planning for increasing flood risk in Canada. It uses a multiple-methods, multi-scalar approach to identify interconnected barriers and drivers that operate across municipal, provincial, and federal levels of government in Vancouver and Surrey, British Columbia. Through a policy content analysis (n = 54) and in-depth interviews with planners and other practitioners (n = 31), the study finds five major barriers to the mainstreaming of climate change adaptation: inadequate collaboration, absence of senior level political leadership, lack of public awareness, insufficient financial and staff capacity, and misalignment of policies within and between levels of government.